Identification of cut8+ and cek1+, a novel protein kinase gene, which complement a fission yeast mutation that blocks anaphase. - Samejima, I (1994)
The fission yeast Schizosaccharomyces pombe [corrected] temperature sensitivity cut8-563 mutation causes chromosome overcondensation and short spindle formation in the absence of sister chromatid separation. The cut8-563 mutation allows cytokinesis before the completion of anaphase, thus producing cells with a cut phenotype. The cut8+ gene product may be required for normal progression of anaphase. Diploidization occurs at the restrictive temperature, and 60 to 70% of the cells surviving after two generations are diploid. These phenotypes are reminiscent of those of budding yeast (Saccharomyces cerevisiae) ctf13 and ctf14 (ndc10) mutations. The cut8+ gene, isolated by complementation of the mutant, predicts a 262-amino-acid protein; the amino and carboxy domains are hydrophilic, while the central domain contains several hydrophobic stretches. It has a weak overall similarity to the budding yeast DBF8 gene product. DBF8 is an essential gene whose mutations result in delay in mitotic progression and chromosome instability. Anti-cut8 antibodies detect a 33-kDa polypeptide. Two multicopy suppressor genes for cut8-563 are identified. They are the cut1+ gene essential for nuclear division, and a new gene (designated cek1+) which encodes a novel protein kinase. The cek1+ gene product is unusually large (1,309 amino acids) and has a 112-amino-acid additional sequence in the kinase domain. The cek1+ gene is not an essential gene. Protein phosphorylation by cek1 may facilitate the progression of anaphase through direct or indirect interaction with the cut8 protein.